Epigenetic Modification Mechanisms Involved in Inflammation and Fibrosis in Renal Pathology - Jose Luis Morgado-Pascual; Vanessa Marchant; Raul Rodrigues-Diez; Nuria Dolade; Beatriz Suarez-Alvarez; Bredford Kerr; Jose M. Valdivielso; Marta Ruiz-Ortega; Sandra Rayego-Mateos (Hindawi Limited, 2018)
The growing incidence of obesity, hypertension, and diabetes, coupled with the aging of the population, is increasing the prevalence of renal diseases in our society. Chronic kidney disease (CKD) is characterized by persistent inflammation, fibrosis, and loss of renal function leading to end-stage renal disease. Nowadays, CKD treatment has limited effectiveness underscoring the importance of the development of innovative therapeutic options. Recent studies have identified how epigenetic modifications participate in the susceptibility to CKD and have explained how the environment interacts with the renal cell epigenome to contribute to renal damage. Epigenetic mechanisms regulate critical processes involved in gene regulation and downstream cellular responses. The most relevant epigenetic modifications that play a critical role in renal damage include DNA methylation, histone modifications, and changes in miRNA levels. Importantly, these epigenetic modifications are reversible and, therefore, a source of potential therapeutic targets. Here, we will explain how epigenetic mechanisms may regulate essential processes involved in renal pathology and highlight some possible epigenetic therapeutic strategies for CKD treatment.